Mono-ubiquitination of Rabphilin 3A by UBE3A serves a non-degradative function - Rossella Avagliano Trezza; A. Mattijs Punt; Edwin Mientjes; Marlene van den Berg; F. Isabella Zampeta; Ilona J. de Graaf; Yana van der Weegen; Jeroen A. A. Demmers; Ype Elgersma; Ben Distel (Scientific Reports, 2021)
Abstract Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by brain-specific loss of UBE3A, an E3 ubiquitin protein ligase. A substantial number of possible ubiquitination targets of UBE3A have been identified, although evidence of being direct UBE3A substrates is often lacking. Here we identified the synaptic protein Rabphilin-3a (RPH3A), an effector of the RAB3A small GTPase involved in axonal vesicle priming and docking, as a ubiquitination target of UBE3A. We found that the UBE3A and RAB3A binding sites on RPH3A partially overlap, and that RAB3A binding to RPH3A interferes with UBE3A binding. We confirmed previous observations that RPH3A levels are critically dependent on RAB3A binding but, rather surprisingly, we found that the reduced RPH3A levels in the absence of RAB3A are not mediated by UBE3A. Indeed, while we found that RPH3A is ubiquitinated in a UBE3A-dependent manner in mouse brain, UBE3A mono-ubiquitinates RPH3A and does not facilitate RPH3A degradation. Moreover, we found that an AS-linked UBE3A missense mutation in the UBE3A region that interacts with RPH3A, abrogates the interaction with RPH3A. In conclusion, our results identify RPH3A as a novel target of UBE3A and suggest that UBE3A-dependent ubiquitination of RPH3A serves a non-degradative function.